2017
DOI: 10.1111/cas.13241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab in Japanese patients with previously untreated advanced melanoma: A phase II study

Abstract: Treating advanced or recurrent melanoma remains a challenge. Cancer cells can evade the immune system by blocking T‐cell activation through overexpression of the inhibitory receptor programmed death 1 (PD‐1) ligands. The PD‐1 inhibitor nivolumab blocks the inhibitory signal in T cells, thus overcoming the immune resistance of cancer cells. Nivolumab has shown promising anticancer activity in various cancers. We carried out a single‐arm, open‐label, multicenter, phase II study to investigate the efficacy and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
111
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 34 publications
6
111
3
Order By: Relevance
“…The results of these studies were consistent with the hypothesis that irAE are associated with a better outcome after this therapy. Several studies including patients treated with nivolumab for melanoma reported that the antitumor response was stronger in those exhibiting irAE . To our knowledge, however, similar findings have not yet been reported in patients with MM who exhibit worse response to nivolumab compared with those with cutaneous melanoma …”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The results of these studies were consistent with the hypothesis that irAE are associated with a better outcome after this therapy. Several studies including patients treated with nivolumab for melanoma reported that the antitumor response was stronger in those exhibiting irAE . To our knowledge, however, similar findings have not yet been reported in patients with MM who exhibit worse response to nivolumab compared with those with cutaneous melanoma …”
Section: Introductionsupporting
confidence: 64%
“…However, the efficacy of nivolumab monotherapy in MM was not known because of its rarity. In Japanese clinical trials of anti‐PD‐1 monotherapy for advanced melanoma, the ORR for nivolumab and pembrolizumab was 34.8% and 24.3%, respectively, whereas the DCR for nivolumab and pembrolizumab was 65.2% and 48.6%, respectively. In comparison, the ORR and DCR in MM were 30% and 56%, respectively, in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS during the entire period of using nivolumab and after switching to ipilimumab was 17.1 months. This result was similar to the median OS of 18.0 months for previously treated melanoma in a Japanese phase II clinical trial . Similarly, OS rate at 18 months was 56.5% for treatment‐naïve melanoma in another Japanese phase II clinical trial …”
Section: Discussionsupporting
confidence: 82%
“…It can therefore be assumed that there are patient groups who are unlikely to respond to anti‐PD‐1 antibody monotherapy or nivolumab plus ipilimumab. In Japanese phase II clinical trials, ORRs to Nivolumab were 28.6% in previously treated advance melanoma and 34.8% in treatment‐naïve advanced melanoma, and ORR of 10.0% and BOR of 20.0% to ipilimumab were reported …”
Section: Discussionmentioning
confidence: 99%
“…Recently, anti‐programmed death 1 (PD‐1) antibody (Ab) monotherapy has been one of the first‐line therapies for the treatment of advanced melanoma, especially for BRAF mutation‐negative melanoma . However, its efficacy rate is 24.1–34.8% in the Japanese population, which is lower than that of a previous clinical trial in another country (43.7%) .…”
Section: Introductionmentioning
confidence: 99%